Optimizing Resource Allocation and Patient Flow: Process Analysis and Reorganization in Three Chemotherapy Outpatient Clinics* - Morgan Holmes, Kelly Bodie, Geoffrey Porter, Victoria Sullivan, Joy Tarasuk, Jodie Trembley and Maureen Trudeau (Healthcare Quarterly, 2010)
Optimizing human and physical resources is a major concern for cancer care decision-makers and practitioners. This issue is particularly acute in the context of ambulatory out patient chemotherapy clinics, especially when – as is the case almost everywhere in the industrialized world – the number of people requiring systemic therapy is increasing while budgets, staffing and physical space remain static. Recent initiatives at three hospital-based chemotherapy units – in Halifax, Toronto and Kingston – shed light on the value of process analysis and reorganization for using existing human and physical resources to their full potential, improving patient flow and enhancing patient satisfaction. The steps taken in these settings are broadly applicable to other healthcare settings and would likely result in similar benefits in those environments.
Keywords: Resource Allocation, Patient Flow, Reorganization, Chemotherapy, Outpatient, systemic therapy regimens